Proceedings of the 2016 2nd International Conference on Artificial Intelligence and Industrial Engineering (AIIE 2016) 2016
DOI: 10.2991/aiie-16.2016.77
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Energy Disaggregation via Deep Learning

Abstract: Abstract-Energy disaggregation is the task of estimating power consumption of each individual appliance from the whole-house electric signals. In this paper, we study this task based on deep learning methods which have achieved a lot of success in various domains recently. We introduce the feature extraction method that uses multiple parallel convolutional layers of varying filter sizes and present an LSTM (Long Short Term Memory) based recurrent network model as well as an auto-encoder model for energy disagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 10 publications
(19 reference statements)
0
33
0
1
Order By: Relevance
“…In the context of the deep neural networks cited in [7][8][9][10], this study performed better than the evaluation metrics used. This is due to the difficulty of other methods in classifying multi-state appliances, such as the dishwasher and the washing machine.…”
Section: Previous Work On Approach Nilm Systemsmentioning
confidence: 87%
See 2 more Smart Citations
“…In the context of the deep neural networks cited in [7][8][9][10], this study performed better than the evaluation metrics used. This is due to the difficulty of other methods in classifying multi-state appliances, such as the dishwasher and the washing machine.…”
Section: Previous Work On Approach Nilm Systemsmentioning
confidence: 87%
“…In [8] the author sought to make an analysis of the various methods of deep learning to improve the performance of a NILM system. In [9], the authors used convolutional neural networks for the task of load disaggregation, promoting the individual identification of equipment loads based on the time series of the aggregate load. In [10], it is shown that CNN networks can also be used in the NILM context for equipment classification based on the VI path of an equipment.…”
Section: Previous Work On Approach Nilm Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [10] the author sought to make an analysis of the various methods of deep learning to improve the performance of a NILM system. In [11], the authors used convolutional neural networks for the task of load disaggregation, promoting the individual identification of equipment loads based on the time series of the aggregate load. In [12], it is shown that CNN networks can also be used in the NILM context for equipment classification based on the VI path of an equipment.…”
Section: Non-intrusive Load Monitoring Systemsmentioning
confidence: 99%
“…Due to this advancement in the area, some researchers have sought to apply as Deep Neural Networks to equipment identification problems in NILM systems. Some works were used in Long Short Term Units (LSTM), Auto-encoder Neural Network and Convolutional Neural Network (CNN) [9][10][11][12], with satisfactory results.…”
Section: Introductionmentioning
confidence: 99%